The Relationship Between Spiritual Leadership, Spiritual Wel-Being And Job Statisfaction In The Malaysian Shipping Industry: A Pilot Study - Mahadzirah, Mohamad; Juhaizi, Mohd Yusof (2014)
Spiritual leadership is a relatively new concept in leadership literature. It aims to intrinsically motivate the leaders and the followers for their spiritual well-being. Job satisfaction is a critical concept with various antecedents and consequences. The situational and dispositional factors or the combination of both factors determine the level of satisfaction of the employees toward their job. This pilot study aims to validate the 26-items of Spiritual leadership Theory scale (SLT) measuring spiritual leadership and spiritual well-being constructs, and 25-items of Abridged Job Descriptive Index taJD11 measuring job satisfaction in the Malaysian shipping industry. The study was conducted among 175 employees of 20 shipping agents companies in the East Coast of Peninsular Malaysia. The results of exploratory factor analysis and confirmatory factor analysis led to some modifications of the survey instruments for future comprehensive research on the spiritual leadership theory in the Malaysian context.